Toxic Workplaces and Employee Performance: The Mediating Role of Organizational Support and Well-being in Java Island - Tanoto, Sherly Rosalina; Edenia, Tita (JMK (Jurnal Manajemen dan Kewirausahaan), 2024)
This study examines the influence of a toxic workplace environment on employee performance, organizational support perception, and employee well-being among workers in Java Island, Indonesia. Utilizing a quantitative research approach, data were collected from 321 permanent employees. Structural Equation Modeling with Partial Least Square (PLS) was employed for analysis. Findings indicate that a toxic workplace environment does not directly impact employee performance, organizational support perception, or employee well-being. However, organizational support perception significantly affects employee performance, and employee well-being also significantly impacts employee performance. Moreover, a toxic workplace environment does not indirectly influence employee performance through organizational support perception or employee well-being as mediating factors. Despite the lack of direct impact, this research contributes novelty by utilizing perception of organizational support and employee well-being as mediating variables for the relationship between toxic workplace environment and employee performance. Practically, the study underscores the importance of addressing organizational support and employee well-being to enhance employee performance in organizations. Managers and organizational leaders must prioritize creating conducive work environments and providing adequate support to foster employee well-being, ultimately leading to improved organizational performance